Development of a sustainable tourism model for Aveiro coastal region (Portugal) - Albuquerque, Helena (2019)
Tourism in coastal areas is the principal tourism activity in Portugal. It is responsible for attracting about 90% of international tourists to our country and the existence of approximately 39,000 direct jobs (European Commission, 2008). It is also largely based in the sun-sea-sand product. However, despite the economic benefits of tourism in these areas, it has also contributed to a loss of characterization, namely through an excessive urban growth without an adequate territorial planning, and to inefficiencies in the socio-economic development, since coastal communities are highly dependent on seasonal economic benefits that tourism provides. In this context, it is important to reflect and to analyse different paradigms that suggest innovative approaches and methodologies to improve sustainable tourism in Portuguese coastal destinations. In this study, it will be presented an analysis of four different planning paradigms (Costa, 2001, Amdam, 2000 and Carr et. al., 2008, UNEP, 2009) that supported the development of a sustainable tourism model for Ria de Aveiro region, a coastal area in central Portugal. These paradigms emphasize the need of combining efficiently the specificities of each destination and the mobilization of available knowledge. The methodology used for this study is literature review of the different concepts concerning coastal tourism, sustainable tourism, tourism development and tourism planning; and the analysis of those four different planning paradigms, in order to design a new tourism model. From this analysis it is possible to define basic assumptions for the sustainable tourism model for Ria de Aveiro region. The integration of these basic assumptions, based on the analysis of these different paradigms, with the territorial analysis also realized, have revealed that it is possible to improve tourism in Ria de Aveiro region, through the sustainable use of endogenous resources, if the different stakeholders (private and public) work together. Thus, it is proposed the establishment of a Development Agency for tourism that promotes the interconnection and the integration of all stakeholders involved in tourism sector. It is also proposed the definition of a sustainable tourism strategy, based on the balance between nature protection and conservation and tourism use of resources.